ชีวิตอิสระของคนพิการทางการเคลื่อนไหวที่ไปได้ด้วยตนเอง : ศึกษากรณีคนพิการที่ขับรถยนต์ส่วนบุคคลในกรุงเทพมหานคร - จันทกานติ์ ฉายะพงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This qualitative research focuses on independent living of mobility disabled drivers in Bangkok. The researcher utilized participant observation and in-depth interviews in order to gain insights into the mobility disabled drivers’ perception. The objectives were to study the influential sources of motive in wanting to become mobility disabled drivers, to examine problems and barriers related to using public transportation that encourage mobility disabled people to drive, to learn about the procedures and related-difficulties in getting the license driver, and most importantly to understand how the mobility disabled Bangkokians view these processes as a part of independent living that help transform their lives. The results showed that the inner motivations were level of self-esteem, self-confident, their positive attitude concerning being ‘disabled.’ On the other hand, external motivations were family support, financial status, and most importantly annoyances regarding problems and barriers of using public transportations. The steps to obtain a driver license for disabled person started from passing the examination and practical test alike people without disability. However, the difficulties were how they have to struggle with the inaccessibility of the testing environment/buildings and costly car modification. In conclusion, the mobility disabled people in this study perceived that driving independently is one of the important parts in help transforming their lives back to normal and feel integrated to the society again.